Strong Convergence Theorems for Mixed Type Asymptotically Nonexpansive Mappings (Communications in Mathematical Research, 2021)
The purpose of this paper is to study a new two-step iterative schemewith mean errors of mixed type for two asymptotically nonexpansive self-mappingsand two asymptotically nonexpansive nonself-mappings and prove strong convergencetheorems for the new two-step iterative scheme in uniformly convex Banach spaces.